The Influence of Training, Work Discipline and Career Development on Employee Performance at the Surabaya Region III Airport Authority Office - Isbandiyah, Yanti; Sundjoto, Sundjoto; Rahayu, Sri (CV. Rayyan Dwi Bharata, 2024)
Companies must continue to improve the quality of human resources to face the increasing competition in various sectors. This research aims to determine the influence of training, work discipline and career development on the performance of employees at the Surabaya Region III Airport Authority Office. This research is included in quantitative research. The method used in this research is a survey method. The data used comes from primary data and secondary data. Data analysis uses multiple regression and classical assumption tests. The research results show that the simultaneous F statistical test results of Training (X1), Work Discipline (X2), and Career Development (X3) on Employee Performance (Y) Tcount is (34.819) F table (2.84) so it means that Training ( X1), Work Discipline (X2), and Career Development (X3) together or simultaneously have an influence on Employee Performance at the Surabaya Region III Airport Authority Office. This means that if the employee feels adequate in terms of training and career development, discipline at work will be created for each employee which will in turn improve good performance.